Particularities of the logistic operations in the pharmaceutical domain - BUTNARU, Ana (Annals of Spiru Haret University. Economic Series, 2010)
The management of logistic operations has a very important role in the case of pharmaceutical products. The purpose of this article is to analyse the particularity of the logistic operations management in the pharmaceutical domain. This is seen in the fact that there is the obligativity of using the exclusive distribution system, because the carriers do not have selling right to the final users. In the pharmaceutical domain, the logistic channels may be represented by a system of vertical marketing, made from producers, en-gross sellers and en-detail sellers that action in the frame of an unified system in which a member of the channel may detain property right over the other members the vertical marketing system may be corporative or contractual. In Romania the medicine producers adopted both marketing systems. Organising and distributing medicine from the specialised unities (pharmaceutical deposit, close circuit pharmacy or comunitary pharmacy) are settled through laws thjat are specific to the pharmaceutical domain. In these conditions the mission of the company is to give medicine with a balance between price – quality – asureness – eficacity, for giving accesibility to different treatments. The role of the state is significant, reason for an interdisciplinary approaching that may drive to ideas, oppinions that may be aplied.